Model Relationship Land Conversion With Carrying Capacity in the Sustainable City Environmental Management Through Dynamic System Method in Jakarta (2016) - Tambaten Yuliana Br Purba (IJEEM - Indonesian Journal of Environmental Education and Management, 2018)
The purpose of the study to predict the environmental sustainability of Jakarta terms of aspects of land conversion and environmental carrying capacity. Using methods dinamyc system. The results showed that the area of open land shrinkage while the land area covered increases, as demand increases while supply remains. Demand for water increases while supply remains, resulting in the exploitable groundwater. Status of environmental carrying capacity of Jakarta in 2016 from the aspect of water is exceeded. Intervention on land and water resources in 2017 is predicted to increase the carrying capacity of land and water, so that the status of the environmental carrying capacity of Jakarta is still ongoing until 2025.